Competitiveness and workforce performance: Asia vis-à-vis the "West". Issue 10 (10th October 2016) - Baumann, Chris; Hamin, Hamin; Tung, Rosalie L.; Hoadley, Susan
Abstract : Purpose: The purpose of this eight-country study is to examine what drives performance at the individual worker's level and compare the explanatory power of such drivers between emerging, newly developed and developed markets around the globe. Design/methodology/approach: The study combines established behavioural theory developed in a Western context with three factors anticipated to be most relevant in Asia (competitive attitude, willingness to serve and speed) as drivers of workforce performance. Four thousand working and middle-class respondents from eight countries were sampled. The associations were tested using structural equation modelling, and workforce performance was measured using univariate analysis. Findings: Three country clusters emerged from the research: emerging economies in Asia (Indonesia, India), where the three factors powerfully explain performance; "Confucian orbit countries" (China, Japan, Korea), where the factors explain 81-93 per cent; and highly developed Western countries (the USA, the UK, Germany), where the factors account for only 20-29 per cent. Practical implications: As well as providing a framework for modelling workforce performance, particularly in Asian countries, the findings indicate that workforce performance should be incorporated in performance indexes. The findings as to which drivers best explain workforce performance in each country can inform workforce recruitment and management, as well as the location of businesses and outsourcing. Originality/value: For the first time, the study addresses the anomaly between economic growth and development experienced by Asian countries and their relatively low rankings in global competitiveness indexes by making the link between workforce performance and country performance.